Inner ear partition - Ars, B. (Online access: Gale., 1998)
PrefaceUp to now, it was generally believed that the destruction of any part of the membranous labyrinth invariably led to complete hearing loss. This concept is no longer accurate!It became apparent that the inner ear was compartmentalized into a cochlea and a vestibule, separated from each other by two valves. Each compartment with its own morphology, physiology, particular biochemistry, and specific pathology. Today, surgery of either of these compartments can be performed without fear for the integrity of the other. This constitutes a revolution in surgery of the inner ear and leads to per.